(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
The aim of the research is to identify the level of social isolation and the level of self-protection among a sample of abused women in displaced families in the governorates of Damascus and Damascus countryside. The relationship between social isolation and their level of self-protection was defined, and the significance of the differences was defined according to the two variables: (social status, educational level). It adopted the descriptive analytical approach. The research sample amounted to (198) single female abusers in displaced families, and the researcher used the social isolation scale prepared by De-Jong Gierveld and Van Tilburg and expressed by (Mohammed, 2000), and the self-protection scale prepared by Prepared by Al-Rashed (2012). The research concluded the following results: There is a statistically significant correlation between social isolation and the level of self-protection among a sample of abused women in displaced families. There are no statistically significant differences between the average scores of the answers of the research sample members on the social isolation scale and the self-protection scale depending on the social status variable. And there were statistically significant differences according to the educational level variable in favor of the battered women whose educational level was (neither reading nor writing).